Reforms of the Gabonese education system: What challenges? - Paulin, MBA Eyeghe Jean (Open Science Journal, 2021)
In the field of education, the idea that an educational system can improve is not just an act of faith. Empirical research in social sciences and organizational management has shown that such improvement can only be achieved through reforms and their efficient implementation. However, studies have shown that, in a similar social context, certain approaches produce opposite effects. This article presents an overview of the reforms of the Gabonese education system from the 1960s to the present day. It has examined the main administrative acts that have framed the content of its reforms, highlighting significant advances in terms of material and social achievements. We noted that the Gabonese education system from the 1960s to the 1970s increased the schooling of young people to more than 90%. Twenty years later, the system was dysfunctional in terms of a shortage of qualified teachers, classrooms and quality of education. Added to this is the high rate of repetition and school failure. Thus, the manner in which education reforms are carried out in Gabon explains the delays noted.